Beeldende kunst : godsdienst - Bouman, Cornelis Adrianus, 1911-1988; Denis, Valentin, 1916-1980; Elffers, Joost, 1946-; Kerssemakers, A. J. M.; Lindyer, G.; Melkman, Jozeph (Amsterdam : Elsevier, 1964)
Prehistoire - Oudheid - Vroege Middeleeuwen - Romaanse kunst - Gotiek - Renassance - Barok en Rococo - 19de eeuw - 20° eeuw